Use the appropriate addition formula to find the exact value of the expression.


  • $\begingroup$ It's the pi sign but I wasn't sure how to make it on this computer $\endgroup$ – user62229 Feb 14 '13 at 1:13
  • $\begingroup$ $\pi$ = $\pi$ $\;\sin\left(\frac{11}{12}\pi\right)$ = $\sin\left(\frac{11}{12}\pi\right)$ $\endgroup$ – Namaste Feb 14 '13 at 1:15
  • $\begingroup$ I was trying to find the derivative but that doesn't seem to work $\endgroup$ – user62229 Feb 14 '13 at 1:20

$(1)$ $$\sin\left(\frac{11}{12}\pi\right) = \sin\left(\frac 5{12}\pi + \frac 6{12} \pi \right) = \sin\left(\frac 5{12}\pi + \frac 12 \pi\right)$$ You can use the sum-of-angles formula for $\sin(a + b)$:

$$\sin(a + b) = \sin(a)\cos(b) + \cos(a)\sin(b)$$

$$\sin\left(\frac 5{12}\pi + \frac 12 \pi\right) = \sin\left(\frac 5{12} \pi\right)\cos\left(\frac 12 \pi\right) + \cos\left(\frac 5{12} \pi\right)\sin\left(\frac 12 \pi\right)$$

$(2)$ Notice that the first term in the sum is multiplied by $\cos\left(\frac{\pi}{2}\right) = 0.$ And since $\sin\left(\frac{\pi}{2}\right) = 1$ you need only compute $\;\cos\left(\frac{5 \pi}{12}\right)\;$. Indeed, seeing that $$\cos\left(\frac{5\pi}{12}\right) = \cos\left(\frac{2\pi}{12} + \frac{3\pi}{12}\right) = \cos\left(\frac{\pi}6 + \frac{\pi}4\right)\tag{1}$$

we can use the "angle-sum formula" for cosine: $$\cos(a + b) = \cos a \cos b - \sin a \sin b$$ $$\cos\left(\frac{\pi}6 + \frac{\pi}4\right) = \cos\left(\frac{\pi}6\right)\cos\left(\frac{\pi}4\right) - \sin\left(\frac{\pi}6\right)\sin\left(\frac{\pi}4\right)$$

Now the computation is one with which you should be familiar: $$\sin\left(\frac{\pi}{6}\right) = \frac12,\;\;\cos\left(\frac{\pi}6\right) = \sqrt 3/2,\;\; \cos\left(\frac{\pi}4 \right) = \sin\left(\frac{\pi}4\right) = 1/\sqrt 2$$

You can scroll over the greyed out line below to check your answer.

$$\;\sin\left(\frac{11 \pi}{12}\right)\;\;=\;\;\frac{\sqrt 3 -1}{2\sqrt 2}$$

You can also use the fact that $$\sin\left(x +\frac {\pi}{2}\right) = \cos(x)$$


Hint: Try $$\sin\left(\frac{2\pi}{12}+\frac{3\pi}{12}+\frac{6\pi}{12}\right).$$From here, use the addition formula, $\sin(\alpha+\beta)=\sin(\alpha)\cos(\beta)+\sin(\beta)\cos(\alpha)$, to get $$\sin\left(\frac{2\pi}{12}+\frac{3\pi}{12}\right)\cos\left(\frac{6\pi}{12}\right)+\sin\left(\frac{6\pi}{12}\right)\cos\left(\frac{2\pi}{12}+\frac{3\pi}{12}\right).$$ As you can see, you will need to use the addition formula one more time, and then note that $$\frac{2\pi}{12}=\frac{\pi}{6},\quad\frac{3\pi}{12}=\frac{\pi}{4},\quad\text{and}\quad \frac{6\pi}{12}=\frac{\pi}{2}.$$

  • $\begingroup$ Do I add them together $\endgroup$ – user62229 Feb 14 '13 at 1:21
  • $\begingroup$ Use the addition formula, $\sin(x+y)=\sin(x)\cos(y)+\sin(y)\cos(x)$. Here, let $x=2\pi/12+3\pi/12$ and $y=6\pi/12$. You will be able to use the sum-angle formula one more time after this application. $\endgroup$ – Clayton Feb 14 '13 at 1:23

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.